Desogestrel-only contraception may reduce headache frequency and improve quality of life in women suffering from migraine. (October 2013) - Merki-Feld, Gabriele S.; Imthurn, Bruno; Seifert, Burkhardt; Merki, Laura L.; Agosti, Reto; Gantenbein, Andreas R.
Abstract Objective To analyse the effects of a three-month course of progestogen-only contraception with desogestrel 75 μg on disability, headache frequency and headache intensity in migraineurs. Materials and methods Migraine disability headache questionnaires (MIDAS) were collected from 37 migraineurs during counselling, and at the end of three months treatment with desogestrel. Another ten women initiated but did not complete treatment. They are included in the overall evaluations of the effect of the regimen on migraine status. Results Desogestrel was associated with significant reductions in headache days and intensity (p < 0.001; p < 0.006), and a significant improvement in quality of life. Days missed at work and days missing leisure activities diminished (p < 0.001; p < 0.001). The MIDAS migraine disability score improved significantly (from 27.4 to 11.1 points) (p < 0.001). While 25 of the 37 women (68%) experienced a decrease of at least one grade, this level of benefit cannot be extrapolated to all initiators. When dropouts are considered, MIDAS grades decrease in 53% (25/47) of the cases. Conclusion The majority of migraineurs experienced a clinically significant reduction in headache frequency and improvement of quality of life with use of desogestrel. Prospective randomised controlled trials are needed to substantiate our results.